Body of Evolution: Visualization of Bodily Characteristics in the Dramatic Dance : of Jaranan Art - Pamungkas, Ari Chandra; Sasanadjati, Jajuk Dwi (Solah, 2025)
Body of Evolution is a choreographic exploration that visualizes human bodily characteristics through a dramatic approach, grounded in the structure of scene divisions within the traditional Jaranan performance from Trenggalek. This work is based on the idea that the evolution of the human body across different stages of life childhood, adolescence, and adulthood, closely aligns with the three core scenes in Jaranan: kiprah, budalan, and perangan. The choreographer interprets these scenes as representations of physical and psychological development. The kiprah scene symbolizes childhood through playful and exploratory movement; budalan reflects adolescence with its curiosity and search for identity; and perangan illustrates adulthood, marked by emotional control and a sense of responsibility. Using a dramatic structure, this piece emphasizes expression, emotion, and bodily language in each scene transition to deliver a strong aesthetic experience for the audience. The primary aim of this creation is to reinforce corporeal language in contemporary performance art based on tradition, while also offering a creative innovation that repositions the existence of Jaranan in today’s modern and entertainment-driven era. Through this work, the choreographer encourages communities and artists to explore local cultural assets in a creative and contextual manner so that traditional arts continue to live and evolve.